Petroleum Degradation by Bacteria Explored from Logending Mangrove Sediments - Apriliani, Herlina; Pramono, Hendro; Oedjijono, Oedjijono; Widodo, Wimbuh Tri; Kristianto, Sonny; Putri, Rury Eryna; Unsunnidhal, Lalu (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2026)
Oil spills resulting from shipping activities, tanker-based oil transportation, and fuel oil usage can cause coastal pollution, particularly in sensitive ecosystems such as mangroves. More than 90% of petroleum consists of hydrocarbons with complex carbon chain structures, making them difficult to decompose. Biological remediation using microorganisms offers a promising alternative for pollution mitigation, as microbes can degrade petroleum components and oxidizing hydrocarbons. This study aimed to evaluate the petroleum-degrading ability of selected bacterial isolates obtained from mangrove sediments at Logending Beach. The research employed experimental and survey methods. The primary parameter measured was Total Petroleum Hydrocarbons (TPH), while supporting parameters included pH and bacterial population density. The study consisted of several stages, including bacterial isolation, screening, and evaluation of the petroleum degradation capacity of selected isolates. The results identified two potential bacterial isolates capable of degrading crude oil. Isolate LG62 exhibited a degradation efficiency of 71.40%, while isolate LG105 showed a degradation efficiency of 57.10%. Petroleum concentrations of 2% (v/v) and 5% (v/v) were degraded more effectively than higher concentrations. Overall, the two bacterial isolates (LG62 and LG105) from Logending mangrove sediments demonstrated significant potential as bioremediation agents for petroleum hydrocarbon contamination.